2022
DOI: 10.3390/cells11101644
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in the Gastrointestinal Tract: Key Contributors to Neuro-Immune Crosstalk and Potential Implications in Disorders of Brain-Gut Interaction

Abstract: Eosinophils are innate immune granulocytes actively involved in defensive responses and in local and systemic inflammatory processes. Beyond these effector roles, eosinophils are fundamental to maintaining homeostasis in the tissues they reside. Gastrointestinal eosinophils modulate barrier function and mucosal immunity and promote tissue development through their direct communication with almost every cellular component. This is possible thanks to the variety of receptors they express and the bioactive molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…Previous research on eosinophils has identified different roles and functions for resident (rEos) and induced (iEos) tissue eosinophils 18 . Intestinal rEos can be distinguished from iEos by their surface receptor expression (intermediate Siglec‐8 levels, a high cluster of differentiation (CD)62L levels, low CD101 levels and not IL‐5 dependent) 19 . At the steady state, intestinal rEos are not allergen‐induced and exhibit an immunosuppressive role, while iEos are antigen‐induced (with high Siglec‐8 and CD101 levels, low CD62L levels, and are IL‐5 dependent), which is proinflammatory 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on eosinophils has identified different roles and functions for resident (rEos) and induced (iEos) tissue eosinophils 18 . Intestinal rEos can be distinguished from iEos by their surface receptor expression (intermediate Siglec‐8 levels, a high cluster of differentiation (CD)62L levels, low CD101 levels and not IL‐5 dependent) 19 . At the steady state, intestinal rEos are not allergen‐induced and exhibit an immunosuppressive role, while iEos are antigen‐induced (with high Siglec‐8 and CD101 levels, low CD62L levels, and are IL‐5 dependent), which is proinflammatory 20 …”
Section: Discussionmentioning
confidence: 99%
“…18 Intestinal rEos can be distinguished from iEos by their surface receptor expression (intermediate Siglec-8 levels, a high cluster of differentiation (CD)62L levels, low CD101 levels and not IL-5 dependent). 19 At the steady state, intestinal rEos are not allergen-induced and exhibit an immunosuppressive role, while iEos are antigen-induced (with high Siglec-8 and CD101 levels, low CD62L levels, and are IL-5 dependent), which is proinflammatory. 20 Eosinophils in homeostasis, as postulated in the Local Immunity And/or Remodeling/Repair (LIAR) hypothesis, 21 are intrinsically homeostatic cells undertaking functional roles in local immunity through inflammation control, tissue remodeling, and epithelial barrier maintenance and repair.…”
Section: Eosinophils In Diverticular Diseasementioning
confidence: 99%
“…Eloísa et al observed increased eosinophilic CRF secretion in the jejunal mucosa of IBS‐D patients, and it was significantly correlated with the severity of symptoms and depressive background [106]. While neuropeptides such as SP were shown to promote eosinophil recruitment and induce degranulation to release CRF, a process independent of the inflammatory pathway [116]. ANS mediates communication between CNS and gut [117].…”
Section: Gut Microbiota Dysbiosis and Intestinal Mucosal Immune Imbal...mentioning
confidence: 99%
“…Eosinophil activation induces the release of active substances from their granules. Eosinophil-derived neurotoxin (EDN), eosinophil cationic protein (ECP), eosinophil peroxidase (EP) and major basic protein (MBP) are among the most studied eosinophil proteins, and are markers of eosinophil activation [79][80][81][82].…”
Section: Eosinophils: Eosinophil-derived Neurotoxin Eosinophilic Cati...mentioning
confidence: 99%